Diseño de una ruta turística comunitaria de aventura y deporte ruta de las cascadas y su influencia en el desarrollo turístico del cantón la Maná y sus zonas aledañas, provincia de Cotopaxi, año 2018 - Herrera Quijije, Honoisa Valeria (2018)
In the present research project an ANALYSIS OF THE CONDITION OF SERVICES OFFERED BY HOTEL DEL RIO AND ITS INCIDENCE HAS BEEN MADE IN THE GUEST SATISFACTION, in this way we tried to obtain real information from the guests to know their criteria about the conditions of the services received and thus be able to improve certain areas for your satisfaction, comfort and loyalty to the Hotel del Rio. Nowadays the competition of hotels and resting places in the Quevedo canton and its surroundings is high, for which reason it is necessary to improve the conditions of the services given within the Hotel; as much as innovation, appearance of staff, entertainment and common areas, which would generate a greater degree of national and foreign guests, benefiting the overall economy of the Hotel, creating more jobs and promoting the tourism sector of the canton. On the other hand we confirm the acceptance of the criteria given by the guests since there are people who before staying not only think about their rest but also to be distracted, relax and be safe, in this way we manage to spread and have an excellent image as reference of lodging at national and international level.